Avaliação da atividade inseticida das folhas de Andira paniculata Benth - Pereira, Ana Paula Nunes (2012)
In Brazil, cutting ants and cartridge corn catter pillars stand out as pests, causing severe damage to agricultura and cause big losses during cultivation of many diverse crops. The usage of vegetable origion substances represents an alternative to control these pests due to being less harmful to the environment. This work presents the study of insecticide activity of the extract of the leaves from Andira paniculata Benth(Fabaceae), though biotesting in cutting ants (Atta sendens rubropilosa) and incarthidge corn catter pillars(Spodoptera frugiperda)with the goal of evaluating its toxic characteristic and insecticide activity, throung in vitro tests. In the toxicity testing to workers of Atta sexdens rubropilosa, the method of incorporation of the plant extract to the artificial diet was the “dry mix”, when these diets were prepared and affered to fifty medium sized workers for 25 days to each treatment. In the insecticide activity of the plant extract over workers of Spodoptera frugiperda( Smith 1787), these were incorporated to an artificial diet described in the literature, following the method of incorporation used to each treatment and a monitoring was held during the development process until the transformation of the pupae into wasps. To workers of Atta sexdens rubropilosa three tested fractions (dichloromethane, hexane, ethyl acetate) caused high mortality rates. In Spodoptera frugiperda there was a meaningful difference only during dichloramethance theatment in the larval stage lasting, being lesser than the control.